Resonance structure and mode transition of quarter‐wave ULF pulsations around the dawn terminator. Issue 6 (1st June 2015) - Obana, Yuki; Waters, Colin L.; Sciffer, Murray D.; Menk, Frederick W.; Lysak, Robert L.; Shiokawa, Kazuo; Hurst, Anthony W.; Petersen, Tanja
Abstract Quarter‐wave modes are standing shear Alfvén waves supported along geomagnetic field lines in space. They are predicted to be generated when the ionosphere has very different conductance between the north compared with the south ionosphere. Our previous observation reported that the resonant frequency is sometimes very low around the dawn terminator and suggested these were due to quarter‐wave modes. In this paper, we examine the resonance structure that provides further evidence of the presence of quarter‐wave modes. Data from three magnetometers in New Zealand were analyzed. Four events are discussed which show extraordinarily low eigenfrequencies, wide resonance widths, and strong damping when the ionosphere above New Zealand was in darkness while the conjugate northern hemisphere ionosphere was sunlit. Later in the morning, the eigenfrequencies and resonance widths changed to normal daytime values. The wide resonance width and the strong damping of the quarter‐wave modes arise from strong energy dissipation in the dark side ionosphere. One event exhibited field line resonance structure continuously through a transition from very low frequency to the normal daytime values. The frequency change began when the dawn terminator passed over New Zealand and finished 1 h later when the ratio of the interhemispheric ionospheric conductances decreased and reached 5. These observations are strong evidence of the presence of quarter‐wave modes and mode conversion from quarter‐ to half‐wave resonances. These experimental results were compared with the ULF wave fields obtained from a 2.5‐dimensional simulation model.